Pengaruh Hipolipidemia Formulasi Tepung Umbi Suweg (Amorphophallus paeoniifolius) dan Tepung Kacang Bogor (Vigna subterranea) terhadap Kadar HDL dan LDL: Hypolipidemic Effect of Suweg Tuber Flour (Amorphophallus paeoniifolius) and Bogor Bean Flour (Vigna subterranea) Formulation on HDL and LDL Levels - Rizka Azkia Rahmania; Qothrunnadaa Fajr Rooiqoh; Ladyamayu Pinasti; Lulu’ Luthfiya (Universitas Airlangga, 2025)
Background: Data from the 2023 Indonesian Health Survey indicate that diabetes mellitus (DM) affects a substantial proportion of the Indonesian among populations aged ≥15 years (11.7%). Among individuals with type 2 diabetes mellitus (T2DM), diabetic dyslipidemia is a prevalent metabolic disorder, particularly characterized by reduced high-density lipoprotein (HDL) levels accompanied by elevated low-density lipoprotein (LDL) levels. Improvement in blood lipid profiles may be supported by the consumption of suweg tubers and Bambara groundnuts as local food sources with high dietary fiber content. Objectives: The present study evaluated the effectiveness of combined suweg tuber and Bambara groundnut flour formulation as dietary interventions to modulate lipid metabolism, specifically focusing on HDL and LDL levels, in rats with diabetes-inducted dyslipidemia. Methods: An experimental approach was conducted using a randomized control group with pre- and post-intervention measurements. Thirty male Sprague-Dawley rats were assigned into five groups: a negative control group (K-), a positive control group (K+), and three treatment groups (F1, F2, and F3) which received formulations at doses of 0.37 g, 0.39 g, and 0.42 g per 200 g BW, respectively. Fasting blood glucose (FBG), HDL, and LDL concentrations were assessed before and after the intervention. Statistical analyses included the Shapiro-Wilk normality test, paired t-test, homogeneity test, and one-way ANOVA, and Tukey Post Hoc analysis. Results: The F1 group had the highest HDL (77.2 ± 2.0 mg/dL) and lowest LDL (27.0 ± 1.5 mg/dL). These differences were statistically significant across groups (p-value < 0.001). Conclusions: The F1 formulation was effective in increasing HDL levels while reducing LDL levels, indicating the potential of suweg tuber and Bambara groundnut flours as functional dietary interventions for diabetic dyslipidemia.